FAKTOR-FAKTOR DETERMINAN PUBLIC TRUST DALAM PELAYANAN DI KANTOR LURAH TANGKERANG TENGAH, PEKANBARU - Farian Praja Saputra (Jurnal Ilmu Administrasi Negara, 2026)
The purpose of this research is to examine the extent of the influence of service quality and community motivation on public trust with community satisfaction functions as an intervening variable within the model at the Tangkerang Tengah Village Office, Pekanbaru City. The research employed a quantitative method using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach with SmartPLS 4.0 software. The sample consisted of 100 respondents selected through probability sampling using the accidental sampling technique. The results show that service quality and community motivation have a positive and significant effect on community satisfaction, while community satisfaction has a positive and significant effect on public trust. The mediation analysis reveals that community satisfaction fully mediates the connection established between service quality and community motivation toward public trust. The SRMR value of 0.079 indicates that the research model meets the goodness of fit criteria. These findings strengthen the New Public Service theory (Denhardt & Janet V. Denhardt, 2000), highlighting the essential role of public engagement and satisfaction in constructing public trust toward the government.